2010
DOI: 10.1186/1475-2875-9-277
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of OptiMal® rapid diagnostic test for malaria in remote areas of the Amazon Region, Brazil

Abstract: BackgroundIn areas with limited structure in place for microscopy diagnosis, rapid diagnostic tests (RDT) have been demonstrated to be effective.MethodThe cost-effectiveness of the Optimal® and thick smear microscopy was estimated and compared. Data were collected on remote areas of 12 municipalities in the Brazilian Amazon. Data sources included the National Malaria Control Programme of the Ministry of Health, the National Healthcare System reimbursement table, hospitalization records, primary data collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…However, treatment compliance has not been considered in this analysis, and also the costs of time parents took off work when looking after a sick child were not included [1]. A study conducted in the Amazon region in Brazil compared the cost-effectiveness of RDT detecting pLDH (OptiMal ® ) and microscopy, with both P. falciparum and P. vivax present [40]. In this study, all components of malaria diagnosis were included: personnel, equipment, maintenance, training and transportation; however, treatment costs and the societal perspective were excluded.…”
Section: P Falciparum and P Vivax Transmissionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, treatment compliance has not been considered in this analysis, and also the costs of time parents took off work when looking after a sick child were not included [1]. A study conducted in the Amazon region in Brazil compared the cost-effectiveness of RDT detecting pLDH (OptiMal ® ) and microscopy, with both P. falciparum and P. vivax present [40]. In this study, all components of malaria diagnosis were included: personnel, equipment, maintenance, training and transportation; however, treatment costs and the societal perspective were excluded.…”
Section: P Falciparum and P Vivax Transmissionmentioning
confidence: 98%
“…When microscopic sensitivity and specificity for P. vivax were 90% and 98%, respectively, and when its sensitivity for P. falciparum was 83%, pLDH RDTs were more cost-effective than microscopy, indicating that very high microscopy accuracy levels are needed for microscopy to be more cost-effective than pLDH RDTs. However, in this study the costs of the antimalarials were not included [40]. Another study conducted in the Amazon region showed that in remote areas HRP-2 RDT was cost-saving compared with microscopy; however, accuracy parameters were not used in this model [41].…”
Section: P Falciparum and P Vivax Transmissionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results were also sensitive to the prevalence of malaria in febrile patients, specificity and sensitivity of the test, cost of testing and medicines, whether nonmalaria febrile illness was a bacterial or selfresolving viral infection, the efficacy of antimalarials and antibiotics taken, and whether patients take medicines as advised [9]. The literature shows that RDTs tend to be more cost-effective than microscopy when compared with a presumptive diagnosis [7,11,12], while the cost-effectiveness of RDTs compared with microscopy depends on the relative cost of the tests, as well as their specificity and sensitivity in routine use [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…In Brazil, the National Malaria Control Programme (NMCP) prescribes the use of RDT solely for remote, difficult to access, endemic areas in the Brazilian Amazon [8]. In these locations, the diagnosis of malaria through microscopic analysis is practically impossible because of harsh environmental conditions combined with limited access to electricity and refrigeration, which are necessary for optimal functioning of sensitive equipment.…”
Section: Introductionmentioning
confidence: 99%